PERANAN KUALITAS AUDIT DALAM HUBUNGAN KEPEMILIKAN MANAJEMEN DAN INFORMATF LABA PERUSAHAAN NON-KEUANGAN INDONESIA - Wisesa, Muhammad Akbar; Saiful, Saiful (UNIB Press, 2018)
This research aimed to determine the effect of management ownership to the informativeness of accounting earnings, with the quality of audit as moderating. The sample consisted of 110 firms (non-financial) listed at Indonesia Stock Exchange from 2012 - 2014 by using a purposive sampling method. The theory in this research is signalling theory. And proxy of the informativeness of accounting earnings is earnings response coefficient (ERC).The results of this research showed the effect of management ownership didn’t negative to the informativeness of accounting earnings. Then, the quality of audit (dummy variable) found moderating the effect of management ownership to the informativeness of accounting earnings.